2015
DOI: 10.1111/dote.12334
|View full text |Cite
|
Sign up to set email alerts
|

Significant understaging is seen in clinically staged T2N0 esophageal cancer patients undergoing esophagectomy

Abstract: This study aimed to determine the impact of preoperative staging on the treatment of clinical T2N0 (cT2N0) esophageal cancer patients undergoing esophagectomy. We reviewed a retrospective cohort of 27 patients treated at a single institution between 1999 and 2011. Clinical staging was performed with computed tomography, positron emission tomography, and endoscopic ultrasound. Patients were separated into two groups: neoadjuvant therapy followed by surgery (NEOSURG) and surgery alone (SURG). There were 11 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…While previous institutional reviews have shown that even though a majority of their patients were receiving both EUS and PET/CT staging, pathologic upstaging after esophagectomy still persisted among 50–60% of cT2N0 patients. [2,3,15] For patients that may have only received one staging modality, the proportions of stage migration may be even higher. Another limitation is the inability to account for all selection biases and factors among patients that receive either induction therapy for cT2N0 esophageal cancer or adjuvant therapy for upstaged upfront cT2N0 esophagectomy patients.…”
Section: Commentmentioning
confidence: 99%
“…While previous institutional reviews have shown that even though a majority of their patients were receiving both EUS and PET/CT staging, pathologic upstaging after esophagectomy still persisted among 50–60% of cT2N0 patients. [2,3,15] For patients that may have only received one staging modality, the proportions of stage migration may be even higher. Another limitation is the inability to account for all selection biases and factors among patients that receive either induction therapy for cT2N0 esophageal cancer or adjuvant therapy for upstaged upfront cT2N0 esophagectomy patients.…”
Section: Commentmentioning
confidence: 99%
“…In this study, we have had a consistent cadre of three experienced general surgeons and two experienced thoracic surgeons who utilized a standard technique across the study period, which should minimize variation. It should also be understood that preoperative staging can be inaccurate, despite the use of current technologies, 21 which is another important limitation in this study. We have used clinical staging as a baseline reference against which to judge the response to neoadjuvant treatment.…”
Section: Discussionmentioning
confidence: 96%
“…One of the concerns of treating patients with T2N0 esophageal cancer is that clinical staging is often inaccurate and the presence of occult nodal disease is missed. Despite advances in staging techniques, understaging rates between 25% and 68% have been reported for patients with cT2N0 esophageal cancer undergoing surgery only …”
Section: Stage‐directed Individualized Therapymentioning
confidence: 99%
“…Owing to the risk of nodal disease and concerns regarding the reliability of current clinical staging techniques, a multimodality treatment approach is recommended by some studies in cT2N0 esophageal cancer patients . However, so far most studies have failed to prove a survival benefit for a multimodality treatment approach compared with a surgery‐alone approach for early‐stage esophageal tumors .…”
Section: Stage‐directed Individualized Therapymentioning
confidence: 99%